2011
DOI: 10.1007/s00394-011-0270-8
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory effects of the mushroom Agaricus blazei and its consequences on atherosclerosis development

Abstract: This is the first in vivo study showing that the immunostimulatory effect of A. blazei has proatherogenic repercussions. A. blazei enhances local and systemic inflammation, upregulating pro-inflammatory molecules, and enhancing leukocyte homing to atherosclerosis sites without affecting the lipoprotein profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…On the other hand, it disagrees with reports on proatherogenic and proinflammatory effects of AbM in a mouse model for atherosclerosis [73] and a clinical randomized trial that found no immunomodulatory effect in elderly women who received dried AbM extract [74]. However, most of the literature supports the anti-inflammatory and anti-allergic findings done with the AbM-based Andosan ingredient.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, it disagrees with reports on proatherogenic and proinflammatory effects of AbM in a mouse model for atherosclerosis [73] and a clinical randomized trial that found no immunomodulatory effect in elderly women who received dried AbM extract [74]. However, most of the literature supports the anti-inflammatory and anti-allergic findings done with the AbM-based Andosan ingredient.…”
Section: Discussionmentioning
confidence: 66%
“…Such receptors are used by APCs to detect pathogen-associated molecular patterns (PAMPs), called pathogen recognition receptors (PRRs) (O'Hagan and de Gregorio, 2009). Likewise, a previous study showed that fruiting bodies of Agaricus blazei present immune stimulatory activity in mice by activating CD4 + T cells, natural killer (NK) cells, and phagocytes, as well as by increasing the production of pro-inflammatory cytokines, such as IFN-γ and TNF-α, using these receptors (Gonçalves et al, 2012). The authors observed that spleen cells of animals exhibited a higher radioactivity of 99m Tecnecium-labeled leukocytes, which was associated with Fig.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, the frequency of activated monocytes and neutrophils was increased in the blood of the Agaricus blazei-treated animals (Gonçalves et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some edible mushrooms have been shown to inhibit the atherosclerotic process, while others have been found to worsen the disease. [21][22][23] The aim of this study was to clarify the effect of Grifola gargal on atherosclerosis using a mouse model of the disease.…”
Section: Introduction Dmentioning
confidence: 99%